Balanced Scorecard em organizações hospitalares : managerialism ou gestão estratégica? - Nunes Junior, Erthelvio Monteiro (2016)
The strategic decision-making process is crucial for organizations because it establishes how to materialize the strategies and ensure the fulfillment of its goals. One of the management practices commonly adopted as support for decision-making and evalua